ECOLOGO-GENETIC MONITORING OF CULTIVATED AND WILD PLANT POPULATION - A. E. SHPAKOV; Yu. A. VOLCHKOV (Юг России: экология, развитие, 2015)
Quantitative estimation of genotypic structure dynamic of three plant species: Nicotiana tabacum L., Anacamptus pyramidalis (L.) Rich., Teucrium chamaedrys L. in different ecological conditions has been conducted. The effectiveness of systemic analyses of the trait complex with the aim of ecologo-genetic monitoring of the plant population has been established.